ANALISIS NILAI TAMBAH PENGOLAHAN SERAI WANGI MENJADI MINYAK ATSIRI PADA KELOMPOK TANI BANGKIT DI DESA SEMOYO KAPANEWON PATUK KABUPATEN GUNUNGKIDUL - Indra Aditiya; Nanang Kusuma Mawardi; Eska Stefani (Fakultas Pertanian UST, 2026)
ABSTRACT This study aims to describe the processing of citronella grass into essential oil and to analyze the value added generated using the Hayami Method at the Bangkit Farmer Group in Semoyo Village, Patuk Sub-district, Gunungkidul Regency. The distillation process is carried out using the water–steam distillation method with a capacity of 300 kg of fresh citronella leaves per cycle, involving three workers with an operating time of approximately six hours, and producing an average yield of 0.7% or equivalent to 2.0–2.1 liters of essential oil per process. The analysis results show that the output value is IDR 2,100 per kg of raw material, with a value added of IDR 1,213 per kg and a value-added ratio of 57.76%. Of the value added generated, labor income amounts to IDR 500 per kg, while the processor’s profit reaches IDR 713 per kg with a profit rate of 58.77%. The findings indicate that the distillation activity generates economic value added for business actors at the farmer group level. This study is expected to serve as a basis for the development of citronella grass processing activities at the Bangkit Farmer Group. Keywords: Citronella, Essential oil, Value added, Hayami Method, Distillation.